Complex management of a patient with refractory primary erythromelalgia lacking a SCN9A mutation - Low, Sarah A (J Pain Res, 2017)
A 41-year-old woman presented with burning and erythema in her extremities triggered by warmth and activity, which was relieved by applying ice. Extensive workup was consistent with adult-onset primary erythromelalgia (EM). Several pharmacological treatments were tried including local anesthetics, capsaicin, ziconotide, and dantrolene, all providing 24–48 hours of relief followed by symptom flare. Interventional therapies, including peripheral and sympathetic ganglion blocks, also failed. Thus far, clonidine and ketamine have been the only effective agents for our patient. Genetic testing was negative for an EM-associated mutation in the SCN9A gene, encoding the Na(V)1.7 sodium channel, suggesting a mutation in an alternate gene.